STYLISTICS OF ARTISTIC SPEECH L.N. TOLSTOY (Innovative Technologica: Methodical Research Journal, 2023)
This article discusses the features of the style of artistic speech, shown on the example of individual fragments of the novel "War and Peace". The author draws attention to the vocabulary used in the novel, which determines the special, unique style of the great writer.